High-throughput sequencing and de novo assembly of Brassica oleracea var. Capitata L. for transcriptome analysis. - Hyun A Kim; Chan Ju Lim; Sangmi Kim; Jun Kyoung Choe; Sung-Hwan Jo; Namkwon Baek; Suk-Yoon Kwon (PLoS ONE)
Background The cabbage, Brassica oleracea var. capitata L., has a distinguishable phenotype within the genus Brassica. Despite the economic and genetic importance of cabbage, there is little genomic data for cabbage, and most studies of Brassica are focused on other species or other B. oleracea subspecies. The lack of genomic data for cabbage, a non-model organism, hinders research on its molecular biology. Hence, the construction of reliable transcriptomic data based on high-throughput sequencing technologies is needed to enhance our understanding of cabbage and provide genomic information for future work. Methodology/principal findings We constructed cDNAs from total RNA isolated from the roots, leaves, flowers, seedlings, and calcium-limited seedling tissues of two cabbage genotypes: 102043 and 107140. We sequenced a total of six different samples using the Illumina HiSeq platform, producing 40.5 Gbp of sequence data comprising 401,454,986 short reads. We assembled 205,046 transcripts (≥ 200 bp) using the Velvet and Oases assembler and predicted 53,562 loci from the transcripts. We annotated 35,274 of the loci with 55,916 plant peptides in the Phytozome database. The average length of the annotated loci was 1,419 bp. We confirmed the reliability of the sequencing assembly using reverse-transcriptase PCR to identify tissue-specific gene candidates among the annotated loci. Conclusion Our study provides valuable transcriptome sequence data for B. oleracea var. capitata L., offering a new resource for studying B. oleracea and closely related species. Our transcriptomic sequences will enhance the quality of gene annotation and functional analysis of the cabbage genome and serve as a material basis for future genomic research on cabbage. The sequencing data from this study can be used to develop molecular markers and to identify the extreme differences among the phenotypes of different species in the genus Brassica.